EFFECT OF FASTING AND RE-FEEDING ON GROWTH PERFORMANCE, BIOCHEMICAL PARAMETERS OF BROWN TROUT (SALMO TRUTTA FARIO) AND RAINBOW TROUT (ONCORHYNCHUS MYKISS) - T. Karata_ (Journal of Animal and Plant Sciences, 2019)
The aim of this study was to investigate the effect of short-term fasting and re-feeding on growth performances, body compositions and biochemical parameters of brown trout (Salmo trutta fario) and rainbow trout (Oncorhynchus mykiss) with an average initial weight of 200±5 g. The 80 brown trout were placed in four tanks. 80 rainbow trout was placed in the other four tanks and 4 different feeding protocols were applied for both species; Control: every day, feeding twice a day; T1: 1 day of deprivation and3 days of re-feeding; T2: 2 days of deprivation and 6 days of re-feeding; T3: 3 days of deprivation and 9 days of re-feeding. Short-term fasting and re-feeding period took 30 days. At the end of the experiment, the weight gain (WG%) and specific growth rate (SGR%) of the control and treatment groups of the rainbow trout were higher than the values of the brown trout (p<0.05). But, no significant differences between the control and treatment groups of both species in terms of biochemical parameters and body compositions were observed (p>0.05). As a result, after the short-term fasting and re-feeding exposure, rainbow and brown trout showed a good growth performance. In addition, these trout could be fed without significant health damage in terms of physiological parameters.
Keywords: Rainbow trout; brown trout; growth; biochemical parameters; body composition; fasting; re-feeding